"You Need to Be Sorted Out With a Knife": The Attempted Online Silencing of Women and People of Muslim Faith Within Academia. (November 2016) - Barlow, Charlotte; Awan, Imran
Academics are increasingly expected to use social media to disseminate their work and knowledge to public audiences. Although this has various advantages, particularly for alternative forms of dissemination, the web can also be an unsafe space for typically oppressed or subordinated groups. This article presents two auto-ethnographic accounts of the abuse and hate academics researching oppressed groups, namely, women and people of Muslim faith, experienced online. In doing so, this article falls into four parts. The first section provides an overview of existing literature, particularly focusing on work which explores the violence and abuse of women and people of Muslim faith online. The second section considers the auto-ethnographic methodological approach adopted in this article. The third section provides the auto-ethnographic accounts of the author's experiences of hate and abuse online. The final section locates these experiences within broader theoretical concepts, such as silencing, and considers possible implications of such online hate in both an academic context and beyond.